Polyarteritis Nodosa in Childhood: Recognition of Early Dermatologic Signs May Prevent Morbidity. Issue 1 (13th August 2013) - Beckum, Kathleen M.; Kim, David J.; Kelly, David R.; Weiser, Peter; Lara, Diego A.; Theos, Amy
Abstract Systemic polyarteritis nodosa (PAN) is a vasculitis that affects small to medium‐size arteries. Onset in childhood is rare and can cause significant morbidity. Often, cutaneous manifestations can provide early clues toward diagnosis. This article describes a case of childhood systemic PAN that presented with fever, a necrotic skin lesion, and oral ulceration. Intestinal perforation complicated this case. Prompt recognition of childhood PAN is important to prevent serious complications.